Personal cell therapy for interstitial cystitis with autologous stromal vascular fraction stem cells - Elliot B. Lander; Mark H. Berman; Jackie R. See (Therapeutic Advances in Urology, 2019)
Background: The objective of this study was to evaluate whether autologous stem-cell-based therapy may mitigate the symptoms of interstitial cystitis. Methods: Stromal vascular fraction (SVF) rich in stem cells and derived from autologous adipose tissue was deployed into 109 men and women with interstitial cystitis/painful bladder syndrome as a surgical procedure. This stem-cell-rich biologic product was injected both systemically and regionally into pelvic floor targets. Patients were queried about quality of life and symptom and bother subjective outcomes tests every 3 months for 2 years. Results: A total of 78 patients reported a positive response at 1 year. Symptom and bother metrics were statistically improved at 1 year. There were minimal adverse events associated with the harvesting, procurement, and clinical deployment of SVF. Conclusion: Interstitial cystitis is a complex clinical problem that is known for its resistance to conventional therapies. SVF as an autologous personalized regenerative strategy shows good safety and efficacy and may potentially have a role in the mitigation of interstitial cystitis.